Predicted distributions and abundances of the sea turtle 'lost years' in the western North Atlantic Ocean. Issue 4 (18th December 2019) - Putman, Nathan F.; Seney, Erin E.; Verley, Phlippe; Shaver, Donna J.; López‐Castro, Melania C.; Cook, Melissa; Guzmán, Vicente; Brost, Beth; Ceriani, Simona A.; Mirón, Raúl de Jesús González Díaz; Peña, Luis Jaime; Tzeek, Miriam; et al.
Abstract : Oceanic dispersal characterizes the early juvenile life‐stages of numerous marine species of conservation concern. This early stage may be a 'critical period' for many species, playing an overriding role in population dynamics. Often, relatively little information is available on their distribution during this period, limiting the effectiveness of efforts to understand environmental and anthropogenic impacts on these species. Here we present a simple model to predict annual variation in the distribution and abundance of oceanic‐stage juvenile sea turtles based on species' reproductive output, movement and mortality. We simulated dispersal of 25 cohorts (1993–2017) of oceanic‐stage juveniles by tracking the movements of virtual hatchling sea turtles released in a hindcast ocean circulation model. We then used estimates of annual hatchling production from Kemp's ridley Lepidochelys kempii (n = 3), green Chelonia mydas (n = 8) and loggerhead Caretta caretta (n = 5) nesting areas in the northwestern Atlantic (inclusive of the Gulf of Mexico, Caribbean Sea and eastern seaboard of the U.S.) and their stage‐specific mortality rates to weight dispersal predictions. The model's predictions indicate spatial heterogeneity in turtle distribution across their marine range, identify locations of increasing turtle abundance (notably along the U.S. coast), and provide valuable context for temporal variation in the stranding of young sea turtles across the Gulf of Mexico. Further effort to collect demographic, distribution and behavioral data that refine, complement and extend the utility of this modeling approach for sea turtles and other dispersive marine taxa is warranted. Finally, generating these spatially‐explicit predictions of turtle abundance required extensive international collaboration among scientists; our findings indicate that continued conservation of these sea turtle populations and the management of the numerous anthropogenic activities that operate in the northwestern Atlantic Ocean will require similar international coordination.